The Case of Non-religious Asylum Seekers. (18th December 2018) - Nixon, Alan
Abstract : In the last ten years there has been increasing focus on the plight of nonreligious and atheist peoples being persecuted in various countries. Some of this focus has come from cases brought to the attention of atheist/humanist organisations such as Atheist Alliance International (AAI), the International Humanist and Ethical Union (IHEU) and local groups. Cases are being reported by the non-religious themselves, from within countries where their views are not acceptable, potentially ending in imprisonment or death. For example, cases have been reported within Saudi Arabia, Afghanistan, Bangladesh, Pakistan, Morocco and Indonesia. There have been general concerns over the status of non-religious and atheist refugees due to the wording of the 1951 Convention Relating to the Status of Refugees. The UN has recently (2016) confirmed the inclusion of non-religious and atheist refugees under the 'religion' criteria, and some countries, such as the UK, Australia and Canada, have accepted refugees based on persecution due to atheism. However, atheism as a criteria is not clearly accepted by all countries of asylum. This article will look at atheist asylum cases, the need for asylum and the structural difficulties faced by atheist/non-religious asylum seekers.